Combined effects of silicon, plant growth-promoting bacteria and arbuscular mycorrhizal fungi on common bean under water deficit stress - Andres Felipe Gaona Acevedo; Juliana Nascimento Rodrigues (Rhizosphere, 2026)

Recovery of betalains from dragon fruit (Hylocereus polyrhizus) peels: Physicochemical properties, thermal stability, and food application - Luisa Maria Figueiredo Lima; Lucas Andre Xavier da Silva; Bruno Augusto Mattar Carciofi; Alcilene Rodrigues Monteiro; Germán Ayala Valencia (Food and Bioproducts Processing, 2026)

Pyridin-3-carbohydrazide strongly impairs Mayaro and Chikungunya virus replication in vitro - Nancy Araceli Juárez Contreras; Natasha Marques Cassani; Mikaela dos Santos Marinho; Giulia Magalhães Ferreira; Maria Eduarda Trevisan Aguillar da Silva; João Victor Rodrigues Dutra; Juliana Roberta Torini; Sainan Wang; Kelyssa Vitória Rodrigues Dantas; Isabela Dolci; Mariana Ortiz de Godoy; Lavinia Cipriano; et al. (Archives of Virology, 2026)
Alphaviruses, including Mayaro virus (MAYV) and Chikungunya virus (CHIKV), pose a growing public health threat, with increasing reports worldwide and no licensed antiviral treatments available. This study evaluated the antiviral activity of pyridine-3-carbohydrazide (P-3-C) against MAYV (strains BeAr and TRVL) and CHIKV (strain La Reunion, LR). Vero E6 or U-2OS cells were infected and treated with P-3-C for 24 h, and cell viability and replication levels were assessed. The 50% cytotoxic concentration (CC 50 ), 50% effective concentration (EC 50 ), and selective index (SI) were calculated. P-3-C showed concentration-dependent activity, strongly inhibiting post-entry stages of MAYV BeAr replication. Treatment reduced intracellular viral RNA levels by 2 log 10 compared with controls and effectively decreased viral RNA release. P-3-C also inhibited MAYV TRVL (SI > 29.4) and CHIKV LR (SI > 48.8) in Vero E6 cells and retained selectivity in U-2OS cells (SI = 3.9 and 6.4, respectively). In a CHIKV U-2OS subgenomic replicon, an SI of 4.1 was found. Additionally, Fluorometric FRET-Based and MicroScale Thermophoresis (MST) assays indicated that P-3-C inhibited the nsP2 protease activity (IC 50 = 12 µM ± 2) and exhibited binding affinity for nsP4 polymerase ( K d = 54 µM ± 1) from CHIKV, thereby suggesting that these non-structural proteins are potential molecular targets. Molecular docking positioned P-3-C within the catalytic pockets of nsP2 and nsP4 of both viruses. Overall, the data suggest that P-3-C exhibits a potential multitarget mechanism of action and highlight its antiviral activity against different alphavirus strains; however, this efficacy could be dependent on the cell line used.

A stepwise methodology for developing fish sperm cryopreservation protocols: application to the endangered Pogonias courbina - Jhony Lisbôa Benato; Nathalia dos Santos Teixeira; Rômulo Batista Rodrigues; Karel Torres Lozano; Renata Villar Dantas; Eduardo Thomé Nicoleti; Gregory Valdivia-Gutiérrez; Leonardo Queiroz de Alencar; Wik Maik Santos Barros; Marcelo Hideo Okamoto; Ricardo Vieira Rodrigues; Luis Andre Sampaio; et al. (Cryobiology, 2026)

Impact of Water Deficit Stress on Starch Characteristics in Potatoes: An Integrative Perspective of Physiological, Biochemical, and Molecular Mechanisms - Andres Felipe Gaona Acevedo; Juan David Ferreira Gomes; Juliana Nascimento Rodrigues; Matheus França Gonçalves; Gabriel Oliveira Ferreira; Rogerio Lopes Vieites (Potato Research, 2026)
Among the most cultivated crops worldwide, potato ( Solanum tuberosum) faces significant threats from water scarcity, owing to its shallow root system and high irrigation requirement. Water deficit disturbs homeostasis and critical physiological mechanisms, including photosynthesis, carbohydrate translocation, and starch metabolism in tuberous plants. It reduces CO₂ assimilation, modulates the expression of key enzymes involved in starch synthesis, such as ADP-glucose pyrophosphorylase and starch synthases, and alters the amylose–amylopectin ratio, consequently affecting their rheological properties. Additionally, drought triggers antioxidant and metabolic responses in plants, including the accumulation of secondary metabolites and the regulation of stress tolerance-related genes. Transcriptomic analyses have revealed water-deficit responsive genes, such as StMAPK11 , StCDPK13 , and StERF94 , which contribute to stress adaptation. This review also explores mitigation strategies and genetic improvement approaches, including the application of biostimulants (chitosan, uniconazole), ZnO and SiO₂ nanoparticles, and the selection of more drought-tolerant genotypes. Recent advances in biotechnology, including gene editing and omics technologies, have contributed to the development of stress-resilient potato varieties.

Tracing environmental contaminants in magellanic penguins: Legacy POPs and metabolic clearance of PAHs - Thales Henrique de Carvalho Storti; Antonio Derley de Sousa Pereira; Cristian Taboada Timoszczuk; Raphael de Lucca Marcello Jarcovis; Lígia Dias de Araujo; Daniela Alves Maia da Silva; Felipe Rodrigues dos Santos; Josilene da Silva; Satie Taniguchi; Rafael Andre Lourenço (Environmental Science and Pollution Research, 2026)
Persistent organic pollutants (POPs) are widespread contaminants that bioaccumulate in the food web, posing risks to wildlife, especially top predators. This study investigates the occurrence of POPs in liver tissues of 23 Magellanic Penguins ( Spheniscus magellanicus ) stranded along the Brazilian coast from June to September 2017. We analyzed concentrations of polychlorinated biphenyls (PCBs), organochlorine pesticides (DDTs, Drins, mirex, endosulfans), and hexachlorobenzene (HCB). POPs were detected in all samples. PCBs and DDTs showed the highest concentrations, with PCBs ranging from < LOD to 199.4 ng g −1 ww (mean: 57.2 ± 49.0 ng g −1 ww), showing a declining trend compared to previous reports. DDT metabolites, especially p,p′-DDE, remained persistent in the samples. HCB was found in 70% of the individuals but at lower levels than previously reported. Other pesticides were present at trace levels, consistent with their historical use in Brazil. No polycyclic aromatic hydrocarbons (PAHs) were detected, which we attribute to rapid metabolic clearance in penguins rather than lack of exposure. This emphasizes the species’ efficiency in eliminating these non-persistent compounds. Our findings highlight the continued presence of legacy POPs in the marine ecosystem and their bioaccumulation in seabirds. Although PCB levels appear to be decreasing, these pollutants still pose ecological risks. Monitoring efforts remain essential, especially considering the potential for re-exposure due to global distillation and melting of polar ice. This study contributes to understanding contaminant dynamics in the Southern Hemisphere and underscores the importance of long-term monitoring of marine wildlife.

Cu(I)-N-Heterocyclic carbenes as potent inhibitors of SARS-CoV-2 replication - Igor Andrade Santos; Josielle V. Fontes; Gustavo C. Rodrigues; Mariana Ortiz de Godoy; Glaucius Oliva; Rafael V. C. Guido; Andres Merits; Camilla Abbehausen; Mark Harris; Ana Carolina Gomes Jardim (BioMetals, 2026)

Physiological and biochemical adjustments in soybean induced by biostimulants application under water deficit stress - Andres Felipe Gaona Acevedo; Juliana Nascimento Rodrigues (South African Journal of Botany, 2026)

Performance analysis and geometric evaluation of galvanized T- and Y-Shapes for earth-air heat exchangers using constructal design - Ana M.B. Domingues; Andre L. Razera; Jairo V.A. Ramalho; Michel K. Rodrigues; Honório J. Fernando; Liércio A. Isoldi; Elizaldo D. dos Santos (Geothermics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

A simulation-based analysis for the road freight transport decarbonization: A case study of Colombia - Cristiam Gil; Andres Rey-Ladino; Gordon Wilmsmeier; Ana María Montes; Emrah Demir; Wessam Abouarghoub; Vasco Sanchez-Rodrigues (Energy and Climate Change, 2025)

Establishing a sperm cryopreservation protocol: Application to the endangered Pogonias courbina - Jhony Lisbôa Benato; Nathalia dos Santos Teixeira; Rômulo Batista Rodrigues; Karel Torres Lozano; Renata Villar Dantas; Eduardo Thomé Nicoletti; Gregory Brayan Valdivia Gutiérrez; Ricardo Vieira Rodrigues; Luis Andre Sampaio; Danilo Pedro Streit (Cryobiology, 2025)

Effects of Lacticaseibacillus rhamnosus LB1.5 as potential probiotic supplement on the liver and adipose tissue of adult male mice to a high-fat diet - Natália Perin Schmidt; Milena Henrique Ferri; Patrícia Molz; Brenda Santos Fraga; Priscila Dutra Silveira; Daiana Rodrigues dos Santos; Juan Andres Cuadro Montanez; Gabriela Merker Breyer; Amanda de Souza da Motta; Marilene Porawski; Alethea Gatto Barschak; Renata Padilha Guedes; et al. (Molecular and Cellular Biochemistry, 2025)

The potential of the CaDef2.1G27-K44 bioinspired peptide to control bacterial disease in Capsicum with a focus on Xanthomonas euvesicatoria - Larissa Maximiano Resende; Érica de Oliveira Mello; Gabriel Bonan Taveira; Anderson Yusei Suzuki Fukuji; Antônio André da Silva Alencar; Claudia Pombo Sudré; Rosana Rodrigues; Andre de Oliveira Carvalho; Katia Valevski Sales Fernandes; Valdirene Moreira Gomes (Journal of Plant Diseases and Protection, 2025)

The role of the P2X7 receptor in inactivated SARS-CoV-2-induced lung injury - N. C. Carvalho-Barbosa; Fabiana Cristina-Rodrigues; Jairo R. Temerozo; Thiago M. L. Souza; Andre L. Gouvêa; Claudio A. Canetti; Eleonora Kurtenbach; Dumith Chequer Bou-Habib; Claudia F. Benjamim; Christina M. Takiya; Luiz E. B. Savio; Robson Coutinho-Silva (Purinergic Signalling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Plasma and ultrasound-treated cashew apple juices: An NMR analysis approach of its sugars, amino and organic acids - Elenilson G. Alves Filho; Lorena M.A. Silva; Kirley M. Canuto; Dayanne Lara Holanda Maia; Sueli Rodrigues; Fabiano Andre Narciso Fernandes (Food Research International, 2025)

In vitro study of essential oils encapsulated in chitosan microparticles against Histoplasma capsulatum and their pathogenicity in Caenorhabditis elegans - Anderson da Cunha Costa; Mirele Rodrigues Fernandes; Augusto Feynman Dias Nobre; Maria Gleiciane Rocha; Jacó Ricarte Lima de Mesquita; Rosemeyre Souza Freire; Andre Jalles Monteiro; Rodrigo Silveira Vieira; Raimunda Sâmia Nogueira Brilhante (Biofouling, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Social immune response reflects infection progression in a soldierless termite - Luiza Helena Bueno da Silva; Aryel C. Goes; Andre Rodrigues; Vincent Fourcassié; Dino McMahon; Ives Haifig (Behavioral Ecology and Sociobiology, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

The APE1/REF-1 and the hallmarks of cancer - Priscyanne Barreto Siqueira; Mariana Moreno de Sousa Rodrigues; Ísis Salviano Soares de Amorim; Thayssa Gomes da Silva; Matheus da Silva Oliveira; Juliana Alves Rodrigues; Adenilson de Souza da Fonseca; Andre Luiz Mencalha (Molecular Biology Reports, 2024)

Disentangling the basidiomycete family Agaricaceae - Pepijn W. Kooij; Meilinda P. Sulastri; Andre Rodrigues; Ester Gaya (Mycological Progress, 2024)

STAT3 Regulates the Redox Profile in MDA-MB-231 Breast Cancer Cells - Juliana Alves Rodrigues; Bruno Ricardo Barreto Pires; Isis Salviano Soares de Amorim; Priscyanne Barreto Siqueira; Mariana Moreno de Sousa Rodrigues; Adenilson de Souza da Fonseca; Carolina Panis; Andre Luiz Mencalha (Cell Biochemistry and Biophysics, 2024)

Culture-dependent methods reveal the diversity of endophytic fungi of Psidium cattleianum leaves (Myrtales: Myrtaceae) - Bianca Lariza Oliveira André; Quimi Vidaurre Montoya; Maria Jesus Sutta Martiarena; Andre Rodrigues (Brazilian Journal of Microbiology, 2024)

Diversity, distribution and phytotoxic and anti-Trypanosoma activities of cultivable fungi associated with Magellan sub-Antarctic strait and Maritime Antarctic macroalgae - Matheus Souto de Freitas; Camila Rodrigues de Carvalho; Franciane Maria Pellizzari; Andres Omar Mansilla; Johanna Marambio; Tânia Maria de Almeida Alves; Silvane Maria Fonseca Murta; Carlos Leomar Zani; Peter Convey; Luiz Henrique Rosa (Extremophiles, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Ecotoxicological strategies employing biochemical markers and organisms to monitor the efficacy of malathion photolysis treatment - Rafaela Imoski; Laís Jarenko da Cruz; Angela Maria Palacio-Cortés; Ana Marta Schafaschek; Eric Schwamberger; Pamella Regina Mariotti; Andre Luis Bichibichi Borges; Fernando Rodrigues-Silva; Liziê Daniela Tentler Prola; Mario Antônio Navarro da Silva; Adriane Martins de Freitas; Marcus Vinicius de Liz (Chemosphere, 2024)

Efficacy of essential oil from ginger (Zingiber officinale) for anesthesia and transport sedation of pacu (Piaractus mesopotamicus) - Anuzhia Paiva Moreira; Fúlvia Cristina Oliveira; Andre Lima Ferreira; Patrini Rodrigues de Almeida; Deliane Cristina Costa; Claudia Andrea Lima Cardoso; Francisco Célio Maia Chaves; Edsandra Campos Chagas; Cristiane Meldau de Campos (Fish Physiology and Biochemistry, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Fungal Cultivars of Higher Attine Ants Promote Escovopsis Chemotropism - Karina B. de Oliveira; Aryel C. Goes; Airton D. Silva; Paulo C. Vieira; Andre Rodrigues (Current Microbiology, 2024)

Insecticidal activity of Capsicum annuum L. leaf proteins on cowpea weevil Callosobruchus maculatus (Coleoptera: Bruchidae) development - Milena Bellei Cherene; Sarah Rodrigues Ferreira; Layrana de Azevedo dos Santos; Rosana Rodrigues; Andre de Oliveira Carvalho; Antônia Elenir Amâncio Oliveira; Valdirene Moreira Gomes (Journal of Asia-Pacific Entomology, 2023)

A meta-analytical review of turbidity effects on fish mobility - Jean N. Rodrigues; Jean C. G. Ortega; Danielle K. Petsch; Andre A. Padial; Dieison A. Moi; Bruno R. S. Figueiredo (Reviews in Fish Biology and Fisheries, 2023)

LDLR and PCSK9 3´UTR variants and their putative effects on microRNA molecular interactions in familial hypercholesterolemia: a computational approach - Renata Caroline Costa de Freitas; Raul Hernandes Bortolin; Jessica Bassani Borges; Victor Fernandes de Oliveira; Carolina Dagli-Hernandez; Elisangela da Silva Rodrigues Marçal; Gisele Medeiros Bastos; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Vivian Nogueira Silbiger; André Ducati Luchessi; Rosario Dominguez Crespo Hirata; et al. (Molecular Biology Reports, 2023)

Unraveling fungal species cultivated by lower attine ants - Salomé Urrea-Valencia; Rodolfo Bizarria Júnior; Pepijn W. Kooij; Quimi Vidaurre Montoya; Andre Rodrigues (Mycological Progress, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Habitat Drives Body Size Evolution in Mustelidae (Mammalia: Carnivora) - Andre Vieira Rodrigues; Laís Aline Grossel; Leonardo Matheus Servino; José Alexandre Felizola Diniz-Filho (Evolutionary Biology, 2023)

Application of essential oils as sanitizer alternatives on the postharvest washing of fresh produce - Jessica S. Pizzo; Jesui V. Visentainer; Andre L.B.R. da Silva; Camila Rodrigues (Food Chemistry, 2023)

Insights about levels and source appointment of petroleum hydrocarbons in Brazilian semi-arid coastal: baseline status assessment for ocean decade targets - Andre Henrique Barbosa de Oliveira; Gabrielle Melo Fernandes; Felipe Rodrigues dos Santos; Narelle Maia de Almeida; Tiago Rocha Nogueira; Diego de Quadros Melo; Laercio Lopes Martins; Rivelino Martins Cavalcante; Ronaldo Ferreira do Nascimento; Christopher Michael Reddy (Environmental Science and Pollution Research, 2023)

Wound dressing using graphene quantum dots: a proof of concept - Vanessa Gonzalez Ferreira Caminha Martins; Luciana Magalhaes Rebelo Alencar; Pedro Filho Noronha Souza; Carolinne Margot Albanez Lorentino; Heloisa Freire Frota; Andre Luis Souza dos Santos; Sara Gemini-Piperni; Veronica Morandi; Vinicius Gonçalves Rodrigues; Jonathas Xavier Pereira; Eduardo Ricci-Junior; Aline Oliveira da Silva de Barros; et al. (Journal of Pharmaceutical Investigation, 2023)

Triazoles with inhibitory action on P2X7R impaired the acute inflammatory response in vivo and modulated the hemostatic balance in vitro and ex vivo - Nathalia Gugick Pinheiro; Daniel Tadeu Gomes Gonzaga; Aldo Rodrigues da Silva; Andre Lopes Fuly; Natalia Lidmar von Ranke; Carlos Rangel Rodrigues; Betina Quintanilha Magalhães; Julianne Soares Pereira; Paulo Anastácio F. Pacheco; Ana Cláudia Silva; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; et al. (Inflammation Research, 2023)

Correction to: Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Increased production of chitinase by a Paenibacillus illinoisensis isolated from Brazilian coastal soil when immobilized in alginate beads - Francenya Kelley Lopes da Silva; Artur Ribeiro de Sa Alexandre; Ariadine Amorim Casas; Maycon Carvalho Ribeiro; Keili Maria Cardoso de Souza; Enio Saraiva Soares; Samuel Rodrigues Dos Santos Junior; Jose Daniel Gonçalves Vieira; Andre Correa Amaral (Folia Microbiologica, 2022)

MicroRNA-149-3p expression correlates with outcomes of adrenocortical tumor patients and affects proliferation and cell cycle progression of H295A adrenocortical cancer cell line - Keteryne Rodrigues da Silva; Luciana Chain Veronez; Carolina Alves Pereira Correa; Régia Caroline Peixoto Lira; Mirella Baroni; Rosane de Paula Silva Queiroz; Sonir Roberto Rauber Antonini; José Andres Yunes; Silvia Regina Brandalise; Luiz Gonzaga Tone; Carlos Alberto Scrideli (Human Cell, 2022)

Nanoencapsulation of unsaturated omega-3 fatty acids as protection against oxidation: A systematic review and data-mining - Maiana da Costa Vieira; Sylvio Andre Garcia Vieira; Jovito Adiel Skupien; Carina Rodrigues Boeck (Critical Reviews in Food Science and Nutrition, 2022)

Yeasts associated with the worker caste of the leaf-cutting ant Atta cephalotes under experimental conditions in Colombia - Carolina Giraldo; Clemencia Chaves-López; Rosanna Tofalo; Roberto Angrisani; Andre Rodrigues; James Montoya-Lerma (Archives of Microbiology, 2022)

Protein-based hydrogelled emulsions and their application as fat replacers in meat products: A review - Camila de Souza Paglarini; Vitor Andre Silva Vidal; Silvana Martini; Rosiane Lopes Cunha; Marise Aparecida Rodrigues Pollonio (Critical Reviews in Food Science and Nutrition, 2022)

5-Aza-2’-deoxycytidine induces a greater inflammatory change, at the molecular levels, in normoxic than hypoxic tumor microenvironment - Ísis Salviano Soares de Amorim; Juliana Alves Rodrigues; Pedro Nicolau; Sandra König; Carolina Panis; Adenilson de Souza da Fonseca; Andre Luiz Mencalha (Molecular Biology Reports, 2021)

Size matters: penis size, sexual maturity and their consequences for giant armadillo conservation planning - Camila Nascimento Luba; Danilo Kluyber; Gabriel Favero Massocato; Nina Attias; Lilja Fromme; Andre Luís Rios Rodrigues; Ana Maria Reis Ferreira; Arnaud Leonard Jean Desbiez (Mammalian Biology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Fungal communities in different aged leaves of Eucalyptus microcorys F. Muell - Lorena Tigre Lacerda; Luís Fernando Pascholati Gusmão; Andre Rodrigues (Brazilian Journal of Botany, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Caste‐ and pesticide‐specific effects of neonicotinoid pesticide exposure on gene expression in bumblebees - Thomas J. Colgan; Isabel K. Fletcher; Andres N. Arce; Richard J. Gill; Ana Ramos Rodrigues; Eckart Stolle; Lars Chittka; Yannick Wurm (Molecular Ecology, 2019)
Social bees are important insect pollinators of wildflowers and agricultural crops, making their reported declines a global concern. A major factor implicated in these declines is the widespread use of neonicotinoid pesticides. Indeed, recent research has demonstrated that exposure to low doses of these neurotoxic pesticides impairs bee behaviours important for colony function and survival. However, our understanding of the molecular‐genetic pathways that lead to such effects is limited, as is our knowledge of how effects may differ between colony members. To understand what genes and pathways are affected by exposure of bumblebee workers and queens to neonicotinoid pesticides, we implemented a transcriptome‐wide gene expression study. We chronically exposed Bombus terrestris colonies to either clothianidin or imidacloprid at field‐realistic concentrations while controlling for factors including colony social environment and worker age. We reveal that genes involved in important biological processes including mitochondrial function are differentially expressed in response to neonicotinoid exposure. Additionally, clothianidin exposure had stronger effects on gene expression amplitude and alternative splicing than imidacloprid. Finally, exposure affected workers more strongly than queens. Our work demonstrates how RNA‐Seq transcriptome profiling can provide detailed novel insight on the mechanisms mediating pesticide toxicity to a key insect pollinator.

Escovopsis kreiselii specialization to its native hosts in the fungiculture of the lower attine ant Mycetophylax morschi - Bruna Cristina Custodio; Andre Rodrigues (Antonie van Leeuwenhoek, 2019)

Soluble Compounds of Filamentous Fungi Harm the Symbiotic Fungus of Leafcutter Ants - Rodolfo Bizarria; Isabela C. Moia; Quimi V. Montoya; Danilo A. Polezel; Andre Rodrigues (Current Microbiology, 2018)

Diversity of endophytic fungi in Eucalyptus microcorys assessed by complementary isolation methods - Lorena T. Lacerda; Luís F. P. Gusmão; Andre Rodrigues (Mycological Progress, 2018)

Fungal Endophyte Communities in Begonia Species from the Brazilian Atlantic Rainforest - Ana M. L. Correia; Simone P. Lira; Marco A. Assis; Andre Rodrigues (Current Microbiology, 2018)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Nature of the interactions between hypocrealean fungi and the mutualistic fungus of leaf-cutter ants - Sadala Schmidt Varanda-Haifig; Tatiane Regina Albarici; Pablo Henrique Nunes; Ives Haifig; Paulo Cezar Vieira; Andre Rodrigues (Antonie van Leeuwenhoek, 2017)

Unraveling Trichoderma species in the attine ant environment: description of three new taxa - Quimi Vidaurre Montoya; Lucas Andrade Meirelles; Priscila Chaverri; Andre Rodrigues (Antonie van Leeuwenhoek, 2016)

Erratum to: Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Amanda Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Bianca Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Escovopsis trichodermoides sp. nov., isolated from a nest of the lower attine ant Mycocepurus goeldii - Virginia E. Masiulionis; Marta N. Cabello; Keith A. Seifert; Andre Rodrigues; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2015)

Thermophilic fungi in the new age of fungal taxonomy - Tássio Brito de Oliveira; Eleni Gomes; Andre Rodrigues (Extremophiles, 2015)

Yeasts found on an ephemeral reproductive caste of the leaf-cutting ant Atta sexdens rubropilosa - Silvio Lovato Arcuri; Fernando Carlos Pagnocca; Weilan Gomes da Paixão Melo; Nilson Satoru Nagamoto; Dirce Leimi Komura; Andre Rodrigues (Antonie van Leeuwenhoek, 2014)

Biological Fenton’s Oxidation of Pentachlorophenol by Aquatic Plants - Andre Rodrigues dos Reis; Yukako Kyuma; Yutaka Sakakibara (Bulletin of Environmental Contamination and Toxicology, 2013)

Intraspecific variation and emendation of Hannaella kunmingensis - Ifeloju Dayo-Owoyemi; Andre Rodrigues; Melissa F. Landell; Patricia Valente; Ulrich G. Mueller; Jesus Pais Ramos; Fernando C. Pagnocca (Mycological Progress, 2013)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)